Variations in vitamin E, phenolic content, and antioxidant properties of different wheat cultivars of South Korea. Issue 4 (2nd October 2017) - Jeong, Beom-Gyun; Chun, Jiyeon; Jung, Jiyoung; Islam, Md. Atiqual; Sharmin, Farhana; Quines, Venus; Choi, Induck; Choi, Sung-Gil
ABSTRACT: The vitamin E, total phenolic content (TPC), and antioxidant activity (AA) profiles of 32 whole wheat cultivars were investigated. Samples were classified based on its hardness ( HW : hard wheat, MW : medium wheat, and SW : soft wheat) for easy identification. Total vitamin E content ranged from 64.38 SW2 to 111.83 MW9 mg/kg; α-tocopherol (6.03 MW13 to 21.98 MW2 mg/kg), β-T (2.14 MW8 to 21.01 MW9 mg/kg), α-tocotrienol (4.28 MW12 to 9.34 MW9 mg/kg), and β-T3 (38.71 MW16 to 61.07 MW9 mg/kg) were the predominant homologs, with β-T3 as the highest. AA ranged from 334.40 MW4 to 584.80 HW4 μmol gallic acid equivalent/kg while TPC varied from 1139.70 SW6 to 2772.60 MW1 μmol GAE/kg. Significant differences in the vitamin E content, TPC, and AA were found among the cultivars regardless of its hardness index. A very weak correlation was found between TPC and AA while a moderate negative correlation was observed between vitamin E content and AA. Results from this study can serve as basis of further studies on the bioactive profiles of Korean wheat cultivars.